2019
DOI: 10.1108/ijaim-11-2018-0128
|View full text |Cite
|
Sign up to set email alerts
|

Online investment forum and the market response around earnings announcement in the Chinese stock markets

Abstract: Purpose This paper aims to study the following two questions. Do earnings announcements stimulate investors to participate in online discussions? Does online investment forum participation affect the market’s reaction to earnings news? Design/methodology/approach The authors collect all the online posts, which were related to the internet service companies and posted in a Chinese financial forum, guba.eastmoney.com (Guba), during the period between June 30, 2008 and December 31, 2015. Multiple linear regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Eastmoney website provides the largest and the most influential financial portal; its effective browsing time accounts for 55.6 per cent of the total effective browsing time in financial portals in China [1]. At present, Eastmoney's internet stock message board is commonly used by researchers who focus on investor communication (Jiang et al, 2016), information diffusion (Ackert et al, 2016;Li et al, 2018;Hao et al, 2019), investor sentiment (Lai et al, 2014) and even investor attention (Huang et al, 2016;Zhang and Tao, 2018), which verifies that big data is a useful information (Coyne et al, 2018) . The CDT is a database of Eastmoney that covers high frequency data of stocks, securities, funds and commodities.…”
Section: Sample and Descriptive Analysis 31 Sample Selectionmentioning
confidence: 99%
“…Eastmoney website provides the largest and the most influential financial portal; its effective browsing time accounts for 55.6 per cent of the total effective browsing time in financial portals in China [1]. At present, Eastmoney's internet stock message board is commonly used by researchers who focus on investor communication (Jiang et al, 2016), information diffusion (Ackert et al, 2016;Li et al, 2018;Hao et al, 2019), investor sentiment (Lai et al, 2014) and even investor attention (Huang et al, 2016;Zhang and Tao, 2018), which verifies that big data is a useful information (Coyne et al, 2018) . The CDT is a database of Eastmoney that covers high frequency data of stocks, securities, funds and commodities.…”
Section: Sample and Descriptive Analysis 31 Sample Selectionmentioning
confidence: 99%
“…In these forums, breaking financial news and stock-related headlines are often heavily discussed and analyzed by online investors, and rumors are also circulated (i.e. before any associated, confirmed news is announced), see Bommel (2003), Li et al (2018) and Hao et al (2019). Antweiler and Frank (2004) have shown that online talk is not just noise; indeed, it also exerts substantial effects on stock-trading activities [2].…”
Section: Introductionmentioning
confidence: 99%
“…Hao et al (2019) examine how aggregate posts affect the market reaction to earnings news using data from the same stock message board as ours. Based on data on 19 firms, they find that more online posts after earnings announcements facilitate the incorporation of earnings surprises into stock prices.8The website is http://guba.eastmoney.com.…”
mentioning
confidence: 99%